Praktik Virtualisasi Ruang Kelas di Masa Pandemi: Penyeragaman, Banking System Freirean dan Literasi - Emmanuel Kurniawan (Jurnal Riset Manajemen Komunikasi, 2023)
Abstract. The Covid-19 pandemic requires schools to adapt health protocols procedures and the logic of pandemic conditions, at all costs. Schools in Indonesia conduct distance learning or e-learning, one of which is in the form of the virtual classroom. It has the potential to improve digital and information literacy among teachers and students, furthermore it could turn the “banking system” learning style to become a more “problem-posing” strategy. However, it seems that virtual classes only use the internet as a support system, not as a learning ecosystem. This paper aims to look at the online learning process carried out by teachers and students in virtual classrooms, through qualitative research with several high school teachers selected by purposive sampling as research subjects. As a result, most informants revealed that virtual classes still referred to offline conventional classrooms with their obstacles such as uniformity, banking system, lack of information literacy, and the internet had not become a learning ecosystem yet. Abstrak. Pandemi Covid-19 mewajibkan sekolah menyesuaikan diri pada protokol kesehatan dan logika pandemi, dengan segala risikonya. Sekolah-sekolah di Indonesia melakukan pembelajaran jarak jauh (PJJ) atau e-learning, salah satunya berupa kelas virtual. Hal ini berpotensi meningkatkan literasi digital dan literasi informasi guru maupun murid lebih dari sekadar digitalisasi sumber belajar, bahkan berpotensi memperbaiki gaya belajar banking system menjadi lebih problem posing strategy. Akan tetapi, tampaknya kelas virtual tersebut hanya memanfaatkan internet sebagai sistem pendukung, bukan sebagai ekosistem belajar. Tulisan ini bertujuan untuk melihat proses pembelajaran online yang dilakukan guru dan murid di kelas virtual, melalui penelitian kualitatif dengan subjek beberapa guru sekolah menengah yang dipilih secara purposeful sampling. Hasilnya, sebagian besar informan mengungkapkan bahwa kelas virtual masih mengacu pada kelas konvensional luring dengan berbagai tantangan seperti penyeragaman, banking system, kurangnya literasi informasi, dan internet belum menjadi ekosistem belajar.